The sex of architecture - Agrest, Diana. (Harry N. Abrams, 1996)
"Other" spaces and "others" / Mary Mcleod -- Missing objects / Catherine Ingraham -- Present tense / Diane Lewis -- Return of the repressed : nature / Diana Agrest -- Case of the death of nature : a mystery / Diana Balmori -- Female fetish urban form / Ann Bergren -- Crimes in and of the city : the Femme fatale as urban allegory / M. Christine Boyer -- Investigating the city : detective fiction as urban interpretation / Margaret Crawford -- Gendered spaces in colonial Algiers / Zeynep Cilek -- La donna emobile : agoraphobia, women, and urban space / Esther Da Costa Meyer -- "Women internet" vs. the "space of tyranny" / Lauretta Vinciarelli -- Matter of matter : a longing for gravity / Jennifer Bloomer -- Battle lines : E.1027 / Beatriz Colomina -- Colomina's web / Sylvia Lavin -- Mirror images : technology, consumption, and the representation of gender in American architecture since World War II / Joan Ockman -- Through the looking glass / Denise Scott Brown -- Not a muse : the client's role at the Rietveld Schroder house / Alice T. Friedman -- Housing for a postmodern world / Ghislaine Hermanuz -- Claiming the public space : the mothers of Plaza de Mayo / Susana Torre -- Politics of underestimation / Marion Weiss -- Confessions in public space / Lynne Breslin -- Diversity by design : feminist reflections on the future of architectural education and practice / Leslie Kanes Weisman -- Resisting the patriarchal norms of professional education / Sharon E. Sutton -- Pen is mightier than the building : writing on architecture 1850-1940 / Diane Favro.